TAFSIR KEBANGKITAN DALAM AL-QUR’AN: STUDI AYAT-AYAT KISAH NABI AYYUB BANGKIT DARI KETERPURUKAN: THE INTERPRETATION OF RESURRECTION IN THE QUR’AN: A STUDY OF THE VERSES ON THE STORY OF PROPHET AYYUB RISING FROM ADVERSITY - Rizki Aminullah; Hasan Luthfy At-Tamimi; Dedi Efendi (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This article examines the concept of rising from adversity in the Qur’an through the study of verses that narrate the story of Prophet Ayyub (Job). In human life, individuals inevitably face various trials such as loss of wealth, physical suffering, and prolonged hardship that may lead to despair. The story of Prophet Ayyub in the Qur’an serves as an important example of patience, strong faith, and reliance upon Allah in facing severe trials. This research aims to analyze the meaning of recovery from hardship as portrayed in Qur’anic verses about Prophet Ayyub. The study employs a library research method with a thematic interpretation (maudhu’i) approach to verses related to the story of Prophet Ayyub found in several chapters of the Qur’an. The findings indicate that Prophet Ayyub’s recovery from adversity was closely related to his extraordinary patience, sincere supplication, and firm trust in Allah’s help. Through this narrative, the Qur’an provides an important lesson that every trial contains wisdom and becomes a means of strengthening faith for those who remain patient and place their trust in Allah.